2014
DOI: 10.1111/bjh.13162
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral sinus venous thromboses in children with acute lymphoblastic leukaemia – a multicentre study from the Nordic Society of Paediatric Haematology and Oncology

Abstract: SummaryWe present a prospective multicentre cohort of 20 children with acute lymphoblastic leukaemia (ALL) and cerebral sinus venous thrombosis (CSVT). The study covers a period of 5 years and comprises 1038 children treated according to the Nordic Society of Paediatric Haematology and Oncology (NOPHO) ALL 2008 protocol. The cumulative incidence of CSVT was 2%. Sixteen of the thromboses were related to asparaginase and 16 to steroids. Most CSVTs occurred in the consolidation phase. Nearly all were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 13 publications
7
86
3
Order By: Relevance
“…Prophylactic anticoagulation did not seem to protect from CNS thrombosis, as it was performed in 90% of patients with CNS thrombosis and in only 64.9% of the patients without CNS thrombosis 29. The 3.1% rate of CNS thrombosis seen in this study is higher than the 1%–2% incidence rate reported in children30 (see Table 2 for additional asparaginase side effects and recommended management).…”
Section: Thrombotic Complicationscontrasting
confidence: 59%
“…Prophylactic anticoagulation did not seem to protect from CNS thrombosis, as it was performed in 90% of patients with CNS thrombosis and in only 64.9% of the patients without CNS thrombosis 29. The 3.1% rate of CNS thrombosis seen in this study is higher than the 1%–2% incidence rate reported in children30 (see Table 2 for additional asparaginase side effects and recommended management).…”
Section: Thrombotic Complicationscontrasting
confidence: 59%
“…Risk factors for TE include the leukemia itself, older age, central line catheters, immobilization, infections, systemic inflammation, and therapy with asparaginase or corticosteroids or both 76, 90, 93, 95, 96 , whereas inherited thrombophilia risk factors, including common germline DNA polymorphisms, do not seem to play a role or at best remain uncertain 96 . The fatality rate of venous TE is highest in children with thromboses in cerebral veins, and studies on the benefits of anti-thrombotic prophylaxis, preferably with the novel oral anti-coagulants, are needed 90, 97, 98 .…”
Section: Thromboembolismsmentioning
confidence: 99%
“…Cerebral venous sinus thrombosis may be seen following the use of L-asparaginase use and/or steroids. 9 …”
Section: Headachementioning
confidence: 99%